The concept of human nature in Noam Chomsky - Madarasz, Norman Roland; Santos, Daniel Peres (Veritas (Porto Alegre), 2018)
One of the constants in Noam Chomsky’s philosophical, linguistic and ethical positions is the existence of what he calls “human nature”. Following Marx, Darwin and last century’s revolutions in the social sciences, human nature has been one of the most contested conceptual holdovers from modern European philosophy. Chomsky’s discoveries and models on syntax and language make up one of the frameworks to most critically offset the traditional moral dimension of human nature. Contrary to most traditions prior to his work, language can no longer be restricted to either mind, soul or spirit. Language, as Chomsky has continually upheld and sharply refined, is a physical and biological process. But how his notion of human nature derives from this process is complex, as he seems to disregard philosophy’s classic analytic delineation between the descriptive causal realm of human nature and the normative axiological extensions of the same concept. In this paper, we seek to examine the philosophical and ontological implications of Chomsky’s claim that human nature derives from the innate dimension of the language faculty. Not only does Chomsky maintain the category of human nature, he also indexes it to the question of freedom. We thereby argue for the coherence of his proposal and show how it operates to weld the perspective of a modal theory of biologically-rooted creativity to innate conditions specific to his theory of language generation. However, we question whether its restriction to humans alone is sustainable from a scientific perspective by putting forth the claim that Chomsky’s science is in fact a radical ontology of social subjectivation. *** O conceito de natureza humana em Noam Chomsky *** Uma das constantes no posicionamento filosófico, linguístico e ético de Noam Chomsky é a existência do que ele chama de “natureza humana”. Seguindo Marx, Darwin e as revoluções do último século nas ciências sociais, a natureza humana tem sido um dos remanescentes conceituais mais contestados da filosofia moderna europeia. As descobertas e os modelos de Chomsky sobre a sintaxe e a linguagem, configuram um dos quadros que mais objeta criticamente a tradicional dimensão moral da natureza humana. Contrária à maioria das tradições anteriores ao seu trabalho, a linguagem não pode mais ser restringida à mente, alma ou ao espírito. Linguagem, como Chomsky tem constantemente defendido e fortemente aperfeiçoado, é um processo físico e biológico. Mas a maneira que sua noção de natureza humana deriva desse processo é complexa, pois ele parece desconsiderar a clássica delineação analítica da filosofia, entre o reino casual descritivo da natureza humana e as extensões axiológico-normativas do mesmo conceito. Neste artigo, nós procuramos examinar as implicações filosóficas e ontológicas da afirmação de Chomsky à qual a natureza humana deriva da dimensão inata da faculdade da linguagem. Chomsky, não só mantém a categoria da natureza humana, como também a indexa à questão da liberdade. Nós, portanto, argumentamos em favor da coerência de sua proposta e mostramos como ela opera para soldar a perspectiva de uma teoria modal da criatividade biologicamente enraizada, com condições inatas específicas de sua teoria da linguagem gerativa. Entretanto, nós questionamos se a restrição dessa somente aos humanos é sustentável a partir de uma perspectiva científica, ao apresentarmos a afirmação de que a ciência de Chomsky é na verdade uma ontologia radical de subjetivação social. Palavras-chave: Chomsky, Noam; natureza humana; faculdade de linguagem; programa biolinguístico; decodificando Chomsky; liberdade.